(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
The article presents the results of fieldwork conducted during 2008 and 2010 within the copper ore of Gez-Gez in Syunik Region. It has been considered the mineralogical and geochemical features of ores and issues of distribution of copper, molybdenum and gold mineralization within the ore field. Horizontal pattern of distribution of mineralization is revealed. Molybdenum and gold-polymetallic mineralization are available in the central parts of the ore field and copper mineralizations are available in the northern and southern parts. In the composition of ores molybdenite, chalcopyrite-molybdenite, chalcopyrite, pyrite-chalcopyrite, chalcopyrite-hematite, gold-polymetallic and arsenopyrit association of minerals are available, which are copper, molybdenum and gold sources.